Ellis‐Van Creveld syndrome: dental management considerations and description of a new oral finding. (1st May 2015) - Hassona, Y.; Hamdan, M.; Shqaidef, A.; Abu Karaky, A.; Scully, C.
ABSTRACT Ellis‐Van Creveld is a rare syndrome with characteristic dental and orofacial findings. Dental management of patients with Ellis‐Van Creveld syndrome can be complicated by the associated skeletal and cardiac abnormalities. Here, we present the dental and orofacial findings in a patient with Ellis‐Van Creveld syndrome, describe a new oral finding, and discuss the dental management considerations.